Metallic Octahedral CoSe2 Threaded by N‐Doped Carbon Nanotubes: A Flexible Framework for High‐Performance Potassium‐Ion Batteries. Issue 10 (7th August 2018) - Yu, Qiyao; Jiang, Bo; Hu, Jun; Lao, Cheng‐Yen; Gao, Yunzhi; Li, Peihao; Liu, Zhiwei; Suo, Guoquan; He, Donglin; Wang, Wei (Alex); Yin, Geping
Abstract: Due to the abundant and low‐cost K resources, the exploration of suitable materials for potassium‐ion batteries (KIBs) is advancing as a promising alternative to lithium‐ion batteries. However, the large‐sized and sluggish‐kinetic K ions cause poor battery behavior. This work reports a metallic octahedral CoSe2 threaded by N‐doped carbon nanotubes as a flexible framework for a high‐performance KIBs anode. The metallic property of CoSe2 together with the highly conductive N‐doped carbon nanotubes greatly accelerates the electron transfer and improves the rate performance. The carbon nanotube framework serves as a backbone to inhibit the agglomeration, anchor the active materials, and stabilize the integral structure. Every octahedral CoSe2 particle arranges along the carbon nanotubes in sequence, and the zigzag void space can accommodate the volume expansion during cycling, therefore boosting the cycling stability. Density functional theory is also employed to study the K‐ion intercalation/deintercalation process. This unique structure delivers a high capacity (253 mAh g −1 at 0.2 A g −1 over 100 cycles) and enhanced rate performance (173 mAh g −1 at 2.0 A g −1 over 600 cycles) as an advanced anode material for KIBs. Abstract : A metallic octahedral cobalt selenide threaded by N‐doping a carbon nanotube framework is synthesized as an anode for potassium‐ion batteries (KIBs). This unique structure with high conductivity, excellent stability, and less agglomeration as well as an intrinsic metallic property can enhance the rate performance and cycling stability for KIBs.